Route 66: The Next Generation Hits The Road - Ryburn-LaMonte, Terri (Teaching History: A Journal of Methods, 1996)
In 1926 construction began on an American institution-Route 66. Upon completion, the highway "reached across more than 2,400 miles, three time zones, and eight states"1 from Chicago to Santa Monica. In time, Route 66 became a symbol of America’s heritage of travel and of our desire to make a better life for ourselves by moving west. The road was especially important to rural areas. Many small, sleepy towns came to life as the road snaked its way through them. Restaurants, gas stations, truck stops, and other businesses sprang up along the road to accommodate the business travelers and vacationers who traveled Route 66. As American grew, with the resulting demand for faster and safer roads, the original two-lane road was replaced by a four-lane highway that closely paralleled the first. This new road generally skirted towns, so some businesses moved closer to the road; others counted on the "Business Route 66" signs to funnel traffic off the new four-lane and into their places of business. Eventually, this four-lane highway was replaced by an even more efficient, and impersonal, pavement: the Interstate. Some towns survived this change better than others.